Structural defence mechanisms in groundnut to late leaf spot pathogen - A.P. SURYAWANSHI, C.D. MAYEE and (Indian Phytopathology, 2002)
Five late leaf spot (LLTS) resistant genotypes of groundnut viz., Nc Ac 17133, PI 259747, PI 381622, PI 390595 and PI 405 132 were screened along with two susceptible cultivars JL-24 and UF 70-103, for morphological and anatomical features. Resistant genotypes were characterized by smaller size stomata of low frequency, compact palisade layer, thicker epidermis-cum-cuticle and presence of trichomes on abaxial surfaces of leaves. Prolonged incubation period of LLS in resistant tissue was a consequencelate appearance of intracellular hyphae, occlusion of intercellular spaces and accumulation of mycelial mass below epidermis. Infection of LLS in susceptible tissues was marked by thickening of palisade cells, formation of swollen cells in a narrow zone some distance away from the site of infection. The chloroplasts normally disappeared in palisade cells before production of dense stroma and conidiophores. Rupturing of epidermal wall was clearly evident. However, in resistant tissues, discreet stroma and late occurrence of epidermal cracks were observed.